Mempertemukan Pendapat Wahabi Salafi dengan Ahlus Sunnah Tentang Sampai atau Tidaknya Pahala Bacaan Surat Al Fatihah Kepada Mayit - Muhammad Amanuddin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this paper is to illustrate the sketch that there has been a different point of view between "Salafi Wahabi" and Ahlus Snnah "in understanding whether or not the reading of Surah al Fatihah to the deceased or to people who have died or not, considering this is important because life after death is one stage of the fourth life after the spirit realm, the mother's womb and this world's realm. The Wahhabi Salafi group is of the opinion that the reward for reading Surah Al Fatihah is not for someone who has died, while the Ahlus Sunnah group argues that the reward has arrived. With this writing, it is hoped that several benefits will be obtained for readers and those who need them, including reducing the fanaticism of the madhab/asabiyah schools, secondly, adding to Islamic treasures and so on. the extent of God's mercy to his servant. In this paper, what we offer is to make a meeting point between the opinions of the Wahhabi Salafi and the Ahlus Sunnah, regarding the above, bearing in mind that each of the two opinions has its own arguments and arguments, therefore, in bringing together the two opinions, the author also uses the argument. and argumentation as a tool and a bridge to compromise the two opinions. , The connecting bridge between the two different opinions include: that Allah has given a sign in the Qur'an so that each of you does good deeds according to their respective beliefs, later Allah will decide on the Day of Judgment about the matter that you are in dispute, and also Allah has said in the hadith qudsi which means, I, namely Allah, will follow the prediction of my servant. Therefore, with the above arguments, it is very possible that Allah will decide on the last day that the two opinions above, namely the Wahhabi Salafi group are right and the opinion of the Ahlus Sunnah group is also not wrong, in other words the two opinions are correct. That is the Bridge to bring together these two opinions as proof of Rahman and Allah's womb, and that is what will be discussed in this paper.